ANALISIS BUTIR SOAL URAIAN MATA KULIAH PENGANTAR AKUNTANSI 1 - Budi Mulyati (FKIP, Universitas Banten Jaya, 2021)
The purpose of this study was to analyze the items in the form of essay items, given as a final exam in subject of introductory accounting 1. This question was given to nineteen students in semester 1 of the 2020-2021 academic year. This study used a descriptive method with a quantitative approach. For the purposes of analysis, the item analysis technique was used, which consisted of an analysis of the level of difficulty of the items and the analysis of the differentiating power of the items. Based on the results of the analysis, the results obtained that the questions made had an index of difficulty level as an easy question of 50% and an average question of 50%. And based on the results of the analysis of the differentiating power index, the questions included as questions that needed to be revised were 33.3% and questions that were not good were 67.7%.